Typologies and Multidimensional Nature of Computer Use for Classroom Instruction in Secondary Education - P., Mwei, K.; K., Too, J.; L., Okioma, M. (International Journal of Educational Technology and Learning, 2019)
Computer technology has proved essential in all sectors of human endeavours such as in industry and business. As a consequence, education has been the main beneficiary of the emergence of the microcomputer being used in financial management, administration and progressively in the classroom for instruction. The experimental phase on the benefits of computer technology for instruction is maturing. This paper explores through reviewing literature the various ways computers have been used in the classroom for instruction and through a pilot study, determine the dimensions of computer use with the help of factor analysis. In the pilot study, a sample of 71 respondents provided usable data. This paper helps us to understand: (a) what is meant by “technology/computer use” in the context of classroom instruction, the view that underpins a user’s actual use of technology; (b) the “evident” or “actual usage” of technology in the classroom for instruction; and (c) the possible dimensions of this use. It is deemed important to bring a common understanding of computer use with respect to information and communication technology integration in pedagogy.